Direct Effect of Terrorism on Economic Growth - Chenini, Tarek; Hamida, Arafet; Lassoued, Tahar (Journal of Ecohumanism, 2024)
The objective of this article is to study the effect of terrorism on economic growth and the transmission mechanisms of this effect. To do this, a simultaneous equation model was applied to panel data for a sample of 31 countries (18 developing and 13 developed). The results of this study show the following: Terrorism has a significant negative impact on economic growth in the case of the entire sample; Unemployment also has a significant negative effect on economic growth in the case of the entire sample; Investment and FDI have positive and significant effects on economic growth in the case of the entire sample; For developed countries, we see that terrorism has no significant effect on economic growth; FDI had a positive and significant impact on economic growth in the case of developed countries; Unlike the case of developing countries, we note that terrorism has a positive and significant impact on economic growth; Unemployment, investment and FDI have a positive and significant impact on economic growth in the case of developing countries. It can be said that terrorism threatens fragile economies more and poses no problem in advanced economies.